Association between caffeine intake and fat free mass index: a retrospective cohort study - Ya-Lan Tian; Xin Liu; Meng-Yao Yang; Yu-Han Wu; Fu-Qiang Yin; Zhen-Tong Zhang; Chao Zhang (Journal of the International Society of Sports Nutrition)
Background Caffeine, identified as a central nervous system stimulant in foods, beverages (coffee, tea, chocolate), and medications, has been focused on its ergogenic properties, enhancing physical performance. The aim of this study was to investigate the association between the caffeine intake (from coffee) and fat-free mass index (FFMI).Materials and Methods We carried out a cohort study that included 3,466 women and 3,145 men aged ≥20 years who were intaking caffeine. Caffeine intake from coffee were obtained from two 24-hour dietary recall interviews. The FFMI was calculated as FFM (kg) divided by height in m2. The caffeine intake was classified into quartiles and combined into 4 groups. Multiple linear regression model analysis and multiple logistic regression model analysis were used to assess associations between the caffeine and FFMI adjusted for potential confounders.Results Among the 2,427 participants, males accounted for 52.4%, and females 47.6%. In multiple linear regression model, Model 1 (unadjusted Model (p = 0.041)) and Model 2 (adjusted for age, race, and BMI (p = 0.006)) in women showed a significant relationship between caffeine intake and FFMI. In multivariable models, caffeine intake and FFMI were significantly different (p < 0.05). In sex subgroups, among females, each quartile of caffeine intake was positively correlated with FFMI levels in the average FFMI group in Model 3 (p < 0.001). In age subgroups, each quartile of caffeine intake was positively correlated with FFMI levels in the average FFMI group in Model 3 for individuals aged 20–40 (p = 0.039) and those aged above 40 (p = 0.016). In drinking status subgroups, if they drunk alcohol, each quartile was positively correlated with FFMI levels in the average FFMI group in Model 3 (p < 0.001).Conclusion Caffeine intake was mainly positively associated with FFMI, especially in women with above levels of FFMI. Longitudinal studies and randomized controlled trials are needed to establish causality and provide evidence-based recommendations regarding caffeine intake to optimize muscle health.